Introducing 'Concept Question' writing assignments into upper-level engineering courses. (2nd November 2021) - Davis, Kirsten A.; Mogg, William A.; Callaghan, David P.; Birkett, Greg R.; Knight, David B.; O'Brien, Katherine R.
ABSTRACT: In this paper, we introduce 'Concept Questions, ' a weekly writing assignment that has been incorporated into multiple upper-level engineering courses at a single university with the intent of enhancing students' conceptual understanding of the course content. To explore the influence of this activity on students in these courses, we compared students' scores on the Concept Question assignments with their final exam scores, analysed students' open-ended responses to questions regarding their learning in the course, and surveyed students who had taken these courses in previous semesters to understand how the Concept Question assignments may have influenced their learning approaches in subsequent courses. Our analysis revealed that students highlighted a variety of learning outcomes from the Concept Questions assignments and their performance on the assignments was correlated with their final exam scores. However, most students did not report that these assignments had changed their learning approaches overall. This paper supports prior work suggesting that such assignments can be helpful in individual engineering courses, but further work is needed to explore student learning across courses.